Work for others, not yourself: Globalization, protectionism and Europe's quest for strategic autonomy - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2020)
Protectionism and mercantilism are yet again at the centre of global economic policy. "America First" is the guiding ethos in a good part of US international economic policy. Beijing is taking a larger stake in China's economy and hand out privileges to domestic firms. Europe is increasingly occupied by achieving "strategic autonomy" and to create European champions at the expense of competition. Old and disreputed economic doctrines are getting a new lease on life. Behind this new orientation in international economic policy stands the old idea that a strong economy is an economy not dependent on others. Human prosperity - our story of rags to riches - tells a very different story. Prosperity is generated when people collaborate and improve our collective intelligence. Open economies are much better at creating wealth because they operate by the principle that people should work for others, not themselves. They specialize - and in the process, they get far more dependent on others. Dependency is a factor of success; economic sovereignty is a sure way of depriving people of opportunity and prosperity.
Keywords: 330; Protektionismus; Souveränität; Wirtschaftliche Macht; Europa